2014
DOI: 10.1111/pan.12553
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anesthesia will supercede inhalational anesthesia in pediatric anesthetic practice

Abstract: Inhalational anesthesia has dominated the practice of pediatric anesthesia. However, as the introduction of agents such as propofol, short-acting opioids, midazolam, and dexmedetomidine a monumental change has occurred. With increasing use, the overwhelming advantages of total intravenous anesthesia (TIVA) have emerged and driven change in practice. These advantages, outlined in this review, will justify why TIVA will supercede inhalational anesthesia in future pediatric anesthetic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 186 publications
1
56
0
3
Order By: Relevance
“…There is relatively little data on the effect of interventions to reduce anxiety prior to IV cannulation in the operating room for induction of anesthesia: Studies of preoperative education, audio/visual distraction, and the use of different premedications have not yielded clear recommendations. The increasing popularity and potential benefits of total IV anesthesia necessitate IV cannulation in the awake child, though children may be more anxious before IV induction compared with inhalational induction of anesthesia . Hence, it is important to evaluate interventions to reduce children's anxiety specifically in this context.…”
Section: Introductionmentioning
confidence: 99%
“…There is relatively little data on the effect of interventions to reduce anxiety prior to IV cannulation in the operating room for induction of anesthesia: Studies of preoperative education, audio/visual distraction, and the use of different premedications have not yielded clear recommendations. The increasing popularity and potential benefits of total IV anesthesia necessitate IV cannulation in the awake child, though children may be more anxious before IV induction compared with inhalational induction of anesthesia . Hence, it is important to evaluate interventions to reduce children's anxiety specifically in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The national postal survey conducted by Hill et al in 2008 showed that a propofol infusion was used at least once a month for anesthesia by only 26% of Consultant members of the Association of Paediatric Anaesthetists of Great Britain and Ireland (APAGBI). In recent years, there has been a drive to improve education and usage of TIVA in children through educational workshops at scientific meetings, formation of TIVA for Tots in the UK in association with the Society for Intravenous Anaesthesia (SIVA), the publication of an increasing number of journal articles and books around the subject, and establishment of a TIVA interest group among APAGBI members.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, understanding of the anaesthetic effect on CPO in the healthy brain must be considered a prerequisite for understanding the pathology and anaesthetic influence in the diseased brain [3]. Total intravenous anaesthesia (TIVA) with a combination of propofol and remifentanil is extensively used during ambulatory surgery, paediatric surgery and neurosurgery in humans [811]. This combination of anaesthetics has several characteristics that preserve cerebrovascular reactivity to CO 2 and autoregulatory mechanisms [1114], and can be a suitable basis anaestesia in experimental CPO studies.…”
Section: Introductionmentioning
confidence: 99%